Catheter malposition analysis of totally implantable venous access port in breast cancer patients - Liu, Wenbo; Han, Qingzheng; Li, Lin; Chi, Jiangrui; Liu, Xinwei; Gu, Yuanting (Frontiers in Surgery, 2023)
Background: To investigate the occurrence of catheter malposition in breast cancer patients undergoing Totally Implantable Venous Access Port (TIVAP) implantation and analyze the effect of TIVAP implantation site on the incidence of catheter malposition. Methods: Clinical data of Breast cancer patients underwent TIVAP implantation in our department from 2017 to 2021 were identified by reviewing the electronic medical records. The catheter malposition rate, location, and management of malposed catheters in TIVAP implantation were analyzed. We divided the patients into the left internal jugular vein（IJV） group and the right IJV group according to the site of TIVAP implantation and compared the difference in the incidence of catheter malposition between the two groups． Results: A total of 1510 catheters were implanted in 1504 patients, of which 16 (1.06%) had catheter malposition. The rate of catheter malposition was 4.96% (7/141) for TIVAP implanted via the left IJV and 0.66% (9/1369) for right IJV, with a statistically significant difference (χ 2 = 18.699, P < 0.05). 743 TIVAPS were implanted in patients with right-sided breast tumor, of which the incidence of catheter malposition was 5.15% (7/136) for TIVAP implanted via left IJV and 0.82% (5/607) for right IJV, with a statistically significant difference (χ 2 = 10.290, p < 0.05). Malposed catheters were found in the subclavian vein, IJV, brachiocephalic vein, internal thoracic vein, undefined collateral veins, and outside the blood vessels. All malposed catheters were successfully adjusted to the proper position by manipulation or percutaneous positioning with the assistance of digital subtraction angiography（DSA）, except for one case whose catheter tip was located outside the vessel was removed the port. Conclusion: The catheter malposition rate of ultrasound-guided TIVAP implantation via IJV is low, and the malposed catheter can be successfully adjusted to the proper position by manipulation or DSA-assisted percutaneous positioning, but the catheter malposition incidence of TIVAP implanted via left IJV is higher than that via the right side.